PORTER’S FIVE FORCES IN ACHIEVING COMPETITIVE ADVANTAGE BY IMPROVING THE ORGANIZATIONAL KNOWLEDGE AND INNOVATIVE SERVICES IN SRI LANKA’S TOURISM INDUSTRY - Mohamed Munas; Dr. Kuruvikulam Chandrasekaran Arun (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In the present context of a challenging business environment, knowledge plays an important role in identifying and analysing the issues in implementing creative solutions leading to the development of tourism industry development atpresent and for the future. The KM framework Porter’s five forces processes of handling intellectual human capital with the promotion of creating, transferring and applying knowledge to increase the capability in achieving competitive advantage over the other firms in the tourism industry with the development of innovativeness. The competitive advantage is about reaching to the highest position in the tourism industry against the competitors in terms of increased financial performance and innovativeness. KM is the key factor accelerating the tourism industrial capability in achieving a competitive advantage. This paper focuses on Porter’s five forces in achieving a competitive advantage to improve the organization’s knowledge and Innovative services in Sri Lanka’s tourism industry.